2022
DOI: 10.1101/2022.11.30.518500
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

ZNF524 directly interacts with telomeric DNA and supports telomere integrity

Abstract: Telomeres are nucleoprotein structures at the ends of linear chromosomes. In humans, they consist of TTAGGG repeats, which are bound by dedicated proteins such as the shelterin complex. This complex blocks unwanted DNA damage repair at telomeres, e.g. by suppressing non-homologous end joining (NHEJ) through its subunit TRF2. We here describe ZNF524, a zinc finger protein that directly binds telomeric repeats with nanomolar affinity and reveal the base-specific sequence recognition by co-crystallization with te… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 90 publications
0
1
0
Order By: Relevance
“…5 C ). Recently, we demonstrated that ZNF524 directly interacts with telomeric DNA and supports telomere integrity, with its ZF2 playing a vital role in telomeric DNA recognition ( 33 ). Furthermore, our recent X-ray structures of ZBTB7A ZF1–4 in complex with the −200 sequence element of the γ-globin gene promoter reveal that its ZF4 recognizes a 3′ C:G nucleotide triplet ( 34 ).…”
Section: Resultsmentioning
confidence: 99%
“…5 C ). Recently, we demonstrated that ZNF524 directly interacts with telomeric DNA and supports telomere integrity, with its ZF2 playing a vital role in telomeric DNA recognition ( 33 ). Furthermore, our recent X-ray structures of ZBTB7A ZF1–4 in complex with the −200 sequence element of the γ-globin gene promoter reveal that its ZF4 recognizes a 3′ C:G nucleotide triplet ( 34 ).…”
Section: Resultsmentioning
confidence: 99%
“…Here, the RxxHxxR motif of ZnF11 recognizes G10G11G12 with Arg589, His592 and Arg595 forming a bidentate hydrogen bond interaction with G12, G11 and G10, respectively. This is equivalent to the interaction of both ZBTB48 and ZNF524 with telomeric repeats 32 and ZBTB10 with the telomeric variant repeat TTGGGG 33 (Figure 2C). However, in contrast to the co-crystal structure with telomeric DNA 31 , ZnF10 does not lie outside of the CIITA e.2 DNA duplex but rather interacts with the phosphate backbone along the major groove (Figure 2B, Supplementary Figure 1).…”
Section: Zbtb48 Interacts With Ciita Piii Via Its Znf10 Znf11 and C-t...mentioning
confidence: 89%